Study of Physical and Mechanical Properties of Fabric Intended for Special Clothing - Sirojiddinova Yakhshigul Ismatillevna; Khamraeva Sanovar Atoevna; Akhmajanova Nozanin (Research Parks Publishing LLC, 2022)
In this article, based on the standard requirements of textile materials, experiments and stable refractory abilities of textile fabrics were identified in laboratory conditions, as well as placed in special clothes of fire-extinguishing workers (air thickening, water resistance, resistance to high temperatures), which can fully meet the requirements of the method of production of refractory fabric.